2022
DOI: 10.1051/0004-6361/202243412
|View full text |Cite
|
Sign up to set email alerts
|

NGC 3314a/b and NGC 3312: Ram pressure stripping in Hydra I cluster substructure

Abstract: Cluster substructure and ram pressure stripping in individual galaxies are among the primary evidence for the ongoing growth of galaxy clusters as they accrete galaxies and groups from their surroundings. We present a multi-wavelength study of the center of the Hydra I galaxy cluster, including exquisite new MeerKAT H i and DECam Hα imaging which reveal conclusive evidence for ram pressure stripping in NGC 3312, NGC 3314a and NGC 3314b through compressed H i contours, well-defined H i tails, and ongoing star f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 179 publications
(244 reference statements)
0
3
0
Order By: Relevance
“…There is an increasing consensus building up in the recent literature that most of the enhanced star formation in RPS galaxies is observed on the ‘leading edge’ of the galaxies (Gavazzi et al, 2015; Vulcani et al, 2018; Hess et al, 2022; Roberts et al, 2022a). Such galaxies, showing an unambiguous tail of material stripped from the disc are often called the ‘jellyfish galaxies’ and are considered to be a product of RPS in clusters.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing consensus building up in the recent literature that most of the enhanced star formation in RPS galaxies is observed on the ‘leading edge’ of the galaxies (Gavazzi et al, 2015; Vulcani et al, 2018; Hess et al, 2022; Roberts et al, 2022a). Such galaxies, showing an unambiguous tail of material stripped from the disc are often called the ‘jellyfish galaxies’ and are considered to be a product of RPS in clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the spatial resolution of our H I VLA data does not allow a mapping of the depletion time, but only the derivation of a global value. Before the advent of MUSE, in fact, RPS was already a well-known mechanism, as H I dedicated studies of nearby clusters already demonstrated how this phenomenon is able to produce galaxies with asymmetric disks, sometimes leading to cold gas tails and to almost completely stripped disks (Kenney & Young 1989;Kenney et al 2004;Chung et al 2007;Cortese et al 2010;Hess et al 2022). Further evidence of stripping has also been detected using X-ray emission (Sun et al 2010;Jachym et al 2017;Campitiello et al 2021;Bartolini et al 2022) and lowfrequency data (Gavazzi 1978;Gavazzi et al 1995;Roberts et al 2021;Ignesti et al 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, cluster galaxies often contain less atomic gas than expected from their optical size or stellar mass and have truncated and/or asymmetric H I disks (Chamaraux et al 1980;Haynes et al 1984;Giovanelli & Haynes 1985;Cayatte et al 1990;Schröder et al 2001;Solanes et al 2001;Waugh et al 2002;Chung et al 2009;Loni et al 2021;Zabel et al 2022). Morever, long tails of atomic gas are commonly observed in cluster galaxies (Bravo-Alfaro et al 2000;Kenney et al 2004;Chung et al 2007;Scott et al 2010;Sorgho et al 2017;Ramatsoku et al 2019;Deb et al 2020;Ramatsoku et al 2020;Healy et al 2021;Deb et al 2022;Hess et al 2022).…”
Section: Introductionmentioning
confidence: 99%